O papel mediador de uma capacidade colaborativa na relação entre a cultura organizacional e o desempenho de novos produtos - Sauan, Patrícia Kawai (2018)
In both academic and corporate environments, there have been debates about the influence of the organizational culture in business. The goal is to discover if culture is one of the factors that generate heterogeneity in firms’ performance and, furthermore, under which circumstances this influence can go up or down. The majority of the researches approaches this relation through a direct path. The contribution of this study is given by the proposition that organizational culture, per se, is not able of generating superior performance, but only through a mediating capability. The theoretical support refers to the Resource-based Theory and the Knowledge-based View. Organizational culture is seen as an importante determinant to build this collaborative capability, as well as the combined influence from both culture and capability on the competitive advantages associated to innovation. The innovation construct considers the amount of new elements embedded in the resources, capabilities and strategies of an organization, related to the initial stages of the new product development process. The performance of such a process is evaluated by the product effectiveness and the product innovativeness. The collaboration capability is seen as the synergy achieved by the simultaneously involvement of the three stakeholders, i.e., customers, suppliers and multifunctional teams, in the initial stages up to the design of a new product. Finally, the various types of organizational cultures are classified using the Competing Values Framework. This framework was tested using the survey data from the High Performance Manufacturing project, including 266 firms from 3 industries in 11 countries. In addition, with the objectives of enriching the discussion of the quantitative empirical results and extracting insights for future studies, a complementary qualitative analysis was carried out from semi- structured interviews with professionals from six companies with different cultural traits. The results present evidences about which types of culture encourage the development of a collaboration capability for stakeholders engagement, as well as the role that such a capability plays as a necessary mediation for the culture to produce positive impact on product effectiveness. It is suggested, as well, that the innovativeness of products with high level of originality probably uses a mechanism other than collaboration. Finally, it is not possible to state that flexible and adaptive firms innovate more than controlled and stable ones.